RANCANGAN SISTEM ORIENTASI EKOR TURBIN ANGIN 50 KW - Atmadi, Sulistyo; Fitroh, Ahmad Jamaludin (Indonesian Journal of Aerospace, 2007)
A fin orientation system for wind turbine with a maximum capacity of 50 kw has been designed. The fin system is designed with for the yawing motion. The method used is based on the moment equilibrium criteria. Eccentricity distance of 10 cm was selected for the design. The location of the fin control is placed at the connection between the generator and the fin bar. The design procedures a fin bar of 6m, with the fin area of 25 m. The center of the fin force is located at 3 m from the nose. Whereas the fin angle to the center of the turbine axis is 21.9 degrees. Keywords: Wind turbin, fin, oreintation.